Extensive data mining uncovers novel diversity among members of the rare biosphere within the Thermoplasmatota - Mara D. Maeke; Xiuran Yin; Lea C. Wunder; Chiara Vanni; Tim Richter-Heitmann; Samuel Miravet-Verde; Hans-Joachim Ruscheweyh; Shinichi Sunagawa; Jenny Fabian; Judith Piontek; Michael W. Friedrich; Christiane Hassenrück (Microbiome)
Abstract Background Rare species, especially of the marine sedimentary biosphere, have long been overlooked owing to the complexity of sediment microbial communities, their sporadic temporal and patchy spatial abundance, and challenges in cultivating environmental microorganisms. In this study, we combined enrichments, targeted metagenomic sequencing, and extensive data mining to uncover uncultivated members of the archaeal rare biosphere in marine sediments. Results In protein-amended enrichments, we detected the ecologically and metabolically uncharacterized class Candidatus Penumbrarchaeia within the phylum Thermoplasmatota. By screening more than 8000 metagenomic runs and 11,479 published genome assemblies, we expanded the phylogeny of Ca. Penumbrarchaeia by 3 novel orders. All six identified families of this class show low abundance in environmental samples characteristic of rare biosphere members. Members of the class Ca. Penumbrarchaeia were predicted to be involved in organic matter degradation in anoxic, carbon-rich habitats. All Ca. Penumbrarchaeia families contain high numbers of taxon-specific orthologous genes, highlighting their environmental adaptations and habitat specificity. Besides, members of this group exhibit the highest proportion of unknown genes within the entire phylum Thermoplasmatota, suggesting a high degree of functional novelty in this class. Conclusions In this study, we emphasize the necessity of targeted, data-integrative approaches to deepen our understanding of the rare biosphere and uncover the functions and metabolic potential hidden within these understudied taxa. Video Abstract